Trilobatin, a Component from Lithocarpus polystachyrus Rehd., Increases Longevity in C. elegans Through Activating SKN1/SIRT3/DAF16 Signaling Pathway - Li, Na; Li, Xi; Shi, Yan-Ling; Gao, Jian-Mei; He, Yu-Qi; Li, Fei; Shi, Jing-Shan; Gong, Qi-Hai (Frontiers in Pharmacology, 2021)
Trilobatin (TLB) is an effective component of Lithocarpus polystachyrus Rehd. Our previous study revealed that TLB protected against oxidative injury in neuronal cells by AMPK/Nrf2/SIRT3 signaling pathway. However, whether TLB can delay aging remains still a mystery. Therefore, the present study was designed to investigate the possible longevity-enhancing effect of TLB, and further to explore its underlying mechanism in Caenorhabditis elegans (C. elegans). The results showed that TLB exerted beneficial effects on C. elegans, as evidenced by survival rate, body movement assay and pharynx-pumping assay. Furthermore, TLB not only significantly decreased ROS and MDA levels, but also increased anti-oxidant enzyme activities including CAT and SOD, as well as its subtypes SOD2 andSOD3, but not affect SOD1 activity, as evidenced by heat and oxidative stress resistance assays. Whereas, the anti-oxidative effects of TLB were almost abolished in SKN1, Sir2.3 and DAF16 mutant C. elegans. Moreover, TLB augmented the fluorescence intensity of DAF16 :: GFP, SKN1::GFP, GST4::GFP mutants, indicating that TLB increased the contents of SKN1, SIRT3 and DAF16 due to fluorescence intensity of these mutants, which were indicative of these proteins. In addition, TLB markedly increased the protein expressions of SKN1, SIRT3 and DAF16 as evidenced by ELISA assay. However, its longevity-enhancing effect were abolished in DAF16, Sir2.3, SKN1, SOD2, SOD3 and GST4 mutant C. elegans than those of non-TLB treated controls. In conclusion, TLB effectively prolongs lifespan of C. elegans, through regulating redox homeostasis, which is, at least partially, mediated by SKN1/SIRT3/DAF16 signaling pathway.